Pengaruh Pelatihan Dan Motivasi Terhadap Produktivitas Kerja Guru Pada SMPN 1 Bululawang Malang - Andika Eka Saputra; Hadi Sunaryo; Pardiman Pardiman (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research purpose to determine from description of work training, work motivation and teacher work productivity at SMPN 1 Bululawang Malang. The method used in this research is quantitative with a descriptive approach and conducted at SMPN 1 Bululawang Malang with total population 37 teachers. Data collection technique used questionnaire with likert scale measurement. Data analysis technique used is validity, reliability, normality, multiple linear regression analysis, multicollinearity, heteroscedasticity, hypothesis F, hypothesis t, and coefficient of determination.The result of this research indicate about work training and work motivation does a significant effect to teacher work productivity at SMPN 1 Bululawang Malang,) Work training does a significant effect to teacher work productivity at SMPN 1 Bululawang Malang, Work motivation does not a significant effect to teacher work productivity at SMPN 1 Bululawang Malang.Keywords : teacher work productivity, work training, work motivation